2017
DOI: 10.1073/pnas.1613625114
|View full text |Cite
|
Sign up to set email alerts
|

Mapping evaporative water loss in desert passerines reveals an expanding threat of lethal dehydration

Abstract: Extreme high environmental temperatures produce a variety of consequences for wildlife, including mass die-offs. Heat waves are increasing in frequency, intensity, and extent, and are projected to increase further under climate change. However, the spatial and temporal dynamics of die-off risk are poorly understood. Here, we examine the effects of heat waves on evaporative water loss (EWL) and survival in five desert passerine birds across the southwestern United States using a combination of physiological dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
215
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(218 citation statements)
references
References 37 publications
2
215
1
Order By: Relevance
“…Recent work on birds supports the idea that exposure to high temperatures can result in dehydration and heat stress related mortality (Albright et al . ; Zhang et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work on birds supports the idea that exposure to high temperatures can result in dehydration and heat stress related mortality (Albright et al . ; Zhang et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the recent work by Albright et al . () who found that small passerines in the Desert Southwest were particularly prone to mortality resulting from the failure to maintain body temperatures below lethal limits. While more research is needed, it is possible that physiological pathways responsible for overheating are related to those involved in interspecific adaptation to temperature extremes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power of evaporative cooling to dissipate heat from the body, in environments in which evaporation can occur freely, probably is limited only by the capacity to consume water to replace that lost (Van Sant, Oufiero, Muñoz‐Garcia, Hammond, & Williams, ). Small endotherms are unlikely to maintain continuous evaporative cooling, because they would have to devote too much time to drinking (Albright et al., ; Crompton, Taylor, & Jagger, ). However, most large mammals do sustain some degree of continuous evaporative cooling, even in environments that would not be considered particularly hot.…”
Section: Evaporative Heat Transfer: Not Necessarily Unsustainablementioning
confidence: 99%
“…Water relationships of birds and the factors that affect them are much less understood than the drivers of BMR and FMR. Yet, FWF is a key characteristic affecting the ability of birds to respond to climate change in arid environments (Albright et al, ; Riddell, Iknayan, Wolf, Sinervo, & Beissinger, ). Our results represent a comprehensive analysis of the environmental factors affecting interspecific variation of FWF in birds.…”
Section: Discussionmentioning
confidence: 99%